DNA Methylation, Preterm Birth and Blood Pressure in African American Children: The DPREG Study - Barcelona, Veronica (J Immigr Minor Health, 2021)
Preterm birth (< 37 weeks) has been associated with high blood pressure (BP) and cardiovascular disease in adulthood. Epigenetic mechanisms may explain how preterm birth influences later BP. In this study, we examined the association between DNA methylation (DNAm), preterm birth and BP in African American children. We recruited 100 children and collected clinical and birth history data. DNA was extracted from saliva and the Illumina EPIC BeadChip was used for epigenetic analyses. Preterm birth was not associated with systolic or diastolic BP. No significant DNAm sites were associated with preterm birth in candidate gene methylation analyses. Body mass index was associated with systolic BP (p = 0.01). We did not observe an effect of preterm birth on DNAm or BP in early childhood. Our study is one of the few, however, to examine these associations among African Americans. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10903-021-01201-y.